Compensation - Gerhart, Barry A.; Newman, Jerry M. (Dubuque, IA : McGraw-Hill Education, 2020)
The new edition of Compensation takes a three-pronged approach to compensation by focusing on theory, research, and practice. 13e continues to emphasise the importance of total compensation and its relevance in achieving sustainable competitive advantage.
PART ONE INTRODUCING THE PAY MODEL AND PAY STRATEGY -- Chapter One: The Pay Model -- Chapter Two: Strategy: The Totality of Decisions -- PART TWO INTERNAL ALIGNMENT: DETERMINING THE STRUCTURE -- Chapter Three: Defining Internal Alignment -- Chapter Four: Job Analysis -- Chapter Five: Job-Based Structures and Job Evaluation -- Chapter Six: Person-Based Structures -- PART THREE EXTERNAL COMPETITIVENESS: DETERMINING THE PAY LEVEL -- Chapter Seven: Defining Competitiveness -- Chapter Eight: Designing Pay Levels, Mix, and Pay -- PART FOUR EMPLOYEE CONTRIBUTIONS: DETERMINING INDIVIDUAL PAY -- Chapter Nine: Pay-for-Performance: The Evidence -- Chapter Ten: Pay-for-Performance Plans -- Chapter Eleven: Performance Appraisals -- PART FIVE EMPLOYEE BENEFITS -- Chapter Twelve: The Benefit Determination Process -- Chapter Thirteen: Benefit Options -- PART SIX EXTENDING THE SYSTEM -- Chapter Fourteen: Compensation of Special Groups -- Chapter Fifteen: Union Role in Wage and Salary Administration -- Chapter Sixteen: International Pay Systems -- PART SEVEN MANAGING THE SYSTEM -- Chapter Seventeen: Government and Legal Issues in Compensation -- Chapter Eighteen: Management: Making It Work.
Previous edition: 2017.
Includes bibliographical references and index.
Keywords: Compensation management